Musculoskeletal pain assessment in participants of a cardiopulmonary and metabolic rehabilitation program - Lima, Daiane Pereira; Bündchen, Daiana Cristine; Sties, Sabrina Weiss; Gonzáles, Ana Inês; Andreato, Leonardo Vidal; Wittkopf, Priscilla; Carvalho, Tales de (Journal of Respiratory and CardioVascular Physical Therapy, 2016)
Background: Patients with cardiovascular diseases associated with musculoskeletal disorders may have pain when participating in Cardiopulmonary and Metabolic Rehabilitation (CPMR). Objective: To determine the presence, quantity, intensity and locations of musculoskeletal pain at rest and during physical exercise before and after CPMR. Methods: The subjects were evaluated by the Locomotor System Assessment Inventory before and after three months of CPMR. Results: 57% of the 37 patients (61 ± 10 years) reported pain at baseline. There was no reduction in the amount of rest pain after three months, but a reduction in the amount of pain during physical exercise (p=0.03). There was no change in pain intensity at rest after CPMR and it worsened from exercise. The most frequently reported local pain at all times was in the lumbar spine and knees. Conclusion: The CPMR program helped reduce the amount of pain during exercise, however, without modifying its intensity.